2022
DOI: 10.1155/2022/6274265
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Body Microbiota and the Regulation of Immunity

Abstract: The microbiome corresponds to the genetic component of microorganisms (archaea, bacteria, phages, viruses, fungi, and protozoa) that coexist with an individual. During the last two decades, research on this topic has become massive demonstrating that in both homeostasis and disease, the microbiome plays an important role, and in some cases, a decisive one. To date, microbiota have been identified at different body locations, such as the eyes, lung, gastrointestinal and genitourinary tracts, and skin, and techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 118 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…A large number of studies have shown that gut microbiota plays an important role in the immune microenvironment and interacts with the intestinal immune system, participating in the development and differentiation of immune cells, and regulating the signaling pathways of immune function. 50 Most cancer types, including CRC, develop from a long period of precancerous lesions, in which host immunity is a key factor in stabilizing the latter. However, precancerous tissues can escape from host immune surveillance in various ways and induce immunosuppression directly or indirectly, promoting the transformation of precancerous lesions into tumors.…”
Section: Relationship Between Intestinal Immune Microenvironment and ...mentioning
confidence: 99%
“…A large number of studies have shown that gut microbiota plays an important role in the immune microenvironment and interacts with the intestinal immune system, participating in the development and differentiation of immune cells, and regulating the signaling pathways of immune function. 50 Most cancer types, including CRC, develop from a long period of precancerous lesions, in which host immunity is a key factor in stabilizing the latter. However, precancerous tissues can escape from host immune surveillance in various ways and induce immunosuppression directly or indirectly, promoting the transformation of precancerous lesions into tumors.…”
Section: Relationship Between Intestinal Immune Microenvironment and ...mentioning
confidence: 99%
“…The decision of secondary prevention to avoid recurrence, particularly in immune-compromised patients, is common clinical question. Researchers defined secondary prevention as continued treatment in a patient who had been suspected to be infected with mucormycosis and responded to therapy or restarted treatment in a patient who had achieved successful disease control and was now immune-competent, but was scheduled for new period of immunosuppression in the absence of a consensus definition [9] . The evidence foundation for treatment decisions such as switching to posaconazole or isavoriconazole to enable outpatient therapy is limited [94] .…”
Section: Updated Guidelines For Treatments Of Cammentioning
confidence: 99%
“…Recently researchers have identified hyperactivation of the cytokine response which mediates inflammation and causes disruption in immune cells henceforth results in significant decline in cluster of differentiation CD4 and CD8 which renders patients susceptible for secondary infection [8] . Researchers indicate that activation of antiviral immunity in tissue micro-environment of infected individuals can facilitate the formation, growth and development of different classes of bacteria [9] . Furthermore, prolonged stay under mechanical ventilation has been identified as potential risk factor for development of mucormycosis [10] .…”
Section: Introductionmentioning
confidence: 99%